Measuring the cohesive law in mode I loading of Eucalyptus globulus - Majano-Majano, Almudena (2019)
This work was undertaken during a short-term scientific stay by the first and second authors at the University of Tras-os-Montes e Alto Douro, within the framework of the research project BIA 2015-64491-P Analysis of the stress relaxation in curved members and new joints solutions for timber Gridshells made out of Eucalyptus globulus, co-financed by the Ministry of Economy and Competitiveness of the Spanish Government and ERDF funds. The short-term stay was supported by a STSM Grant from COST Action FP1402 Basis of Structural Timber Design-from research to standards, ref. COST-STSM-ECOST-STSM-FP1402-091116-080058. This work is also supported by: European Investment Funds by FEDER/COMPETE/POCI-Operacional Competitiveness and Internacionalization Programme, under Project POCI-01-0145-FEDER-006958 and National Funds by FCT-Portuguese Foundation for Science and Technology, under the project UID/AGR/04033/2013.